Estudio de verificación del cumplimiento del plan de manejo ambiental del relleno sanitario de la mancomunidad Pujili – Saquisili de provincia de Cotopaxi. - Toro, Adrián (2019)
The case study was carried out in the City of Pujilì at the Pujili - Saquisilì Community Landfill, in the project to verify compliance with the Pujili - Saquisili Community landfill Environmental Management Plan, which is located in the neighborhood Oriente, of the canton Pujilì, being the main objective, the application of an environmental audit of compliance with the Environmental Management Plan that was carried out based on current environmental regulations, and at the same time an analysis was applied to each program of the current Environmental Management Plan in this project, which allows us to disseminate the current situation in which environmental management is based on the results that were obtained after the audit. The first thing that was proceeded was the diagnosis of the current situation of the project, for which it was carried out, field trips, talks with the workers and bibliographic review to obtain the most relevant information of the project, after having finished the diagnosis, it began with the analysis of each of the programs stipulated in the Environmental Management Plan, through a check-list, bibliographic review and field trips, which allowed obtaining data from the programs established in the Environmental Management Plan, in which are not fully complied with the provisions of the law. It was concluded with a list of minor nonconformities (NC-) that are present in the Environmental Management Plan that the project has.